A case study of the Philippine foundation of rural broadcasters and its role in development communication - Arceo, Ma. Arlyn L. (Quezon City University of the Philippines Diliman, 1989)
In 1981, three principal organizations of broadcasters and media men whose aim was to disseminate news to help in the development of rural areas and its folks got together to form one organization. This was the beginning of the Philippine Foundation of Rural Broadcasters (FRB). The objective of this study is to find out what the FRB is as an organization and determine its role in development communication.

Interviews were conducted among five officers and board members stationed in Metro Manila. To determine its role as a disseminator of development information part of the study was devoted to content analyzing the foundation's weekly newsletter where members get their information and materials for broadcast. The study also includes a discussion on the tapes it distributes among its members.

Findings of the study reveal that as an organization, the foundation serves as an effective channel of information through the programs of its members. As information disseminators, it tries to strike a balance among topics of general information and not solely news on farm technologies. Presentation of articles was found to be a balance between English and Filipino.

The objective of organizing these broadcasters for better communication among people serves its purpose.
Thesis
Keywords: Communication in rural development -- Philippines; Broadcasting -- Social aspects -- Philippines